2016
DOI: 10.1080/10489223.2016.1179743
|View full text |Cite
|
Sign up to set email alerts
|

Input frequency and the acquisition of syllable structure in Polish

Abstract: This paper examines phonological development and its relationship to input statistics. Using novel data from a longitudinal corpus of spontaneous child speech in Polish, we evaluate and Downloaded by [Fondren Library, Rice University] at 00:54 15 June 2016A c c e p t e d M a n u s c r i p t 2 compare the predictions of a variety of input-based phonotactic models for syllable structure acquisition. We find that many commonly examined input statistics can make dramatically different predictions, as do different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 85 publications
0
16
0
1
Order By: Relevance
“…Thus, while the role of statistics is indisputable, the necessity, nature and strength of any universal biases are unclear, and actively debated. Complicating the picture is the fact that universal principles are often mirrored by language-particular statistics (Levelt & van de Vijver 2004, Zamuner et al 2005, Jarosz 2010, Jarosz et al to appear), which makes it difficult to disentangle the independent contribution of universal biases and statistics in any particular case. What remains controversial, then, is the extent to which linguistic knowledge can be reduced to experience with the language input.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while the role of statistics is indisputable, the necessity, nature and strength of any universal biases are unclear, and actively debated. Complicating the picture is the fact that universal principles are often mirrored by language-particular statistics (Levelt & van de Vijver 2004, Zamuner et al 2005, Jarosz 2010, Jarosz et al to appear), which makes it difficult to disentangle the independent contribution of universal biases and statistics in any particular case. What remains controversial, then, is the extent to which linguistic knowledge can be reduced to experience with the language input.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated that speakers have knowledge of constraints on consonant clusters (the sonority sequencing principle) (Berent & Lennertz, 2010; Berent et al, 2009), even when the speakers of the language have no experience with clusters (Berent et al, 2008). Input statistics alone often make incorrect predictions about speaker representations, but when combined with abstract representations, make the appropriate predictions about learnability (Jarosz et al, 2017).…”
mentioning
confidence: 99%
“…The above description of top-down inferences, which are detached from the functional aspects of the bottom-up route, echo models of the language user as a statistical learner (see, e.g., Christiansen & Curtin, 1999;Frisch & Zawaydeh, 2001;Tremblay, Baroni, & Hasson, 2013) and, more specifically, they are very much in line with models of phonotactic learners (see, e.g., Coleman & Pierrehumbert, 1997;Albright, 2009;Bailey & Hahn, 2001;Daland et al, 2011;Hayes, 2011;Hayes & Wilson, 2008;Jarosz, Calamaro, & Zentz, 2017;Mayer & Nelson, 2019;Vitevitch & Luce, 2004).…”
Section: Complementary Cognitive Modelsmentioning
confidence: 70%